Revealing cerebrospinal fluid biomarkers in Parkinson's disease dementia based on iTRAQ proteomics research - Han, Lin; Liu, Ying; Tan, Changhong; Mo, Lijuan; Su, Huahua; Ma, Ping; Zeng, Guotao; Yue, Jianhe; Liu, Xi; Chen, LiFen (Frontiers in Neuroscience, 2025)
BackgroundParkinson's disease dementia (PDD) imposes a significant burden on patients and healthcare systems but currently lacks specific biomarkers. This study aimed to identify novel cerebrospinal fluid (CSF) biomarkers for PDD using proteomics and to explore their functional significance.MethodsEmploying iTRAQ-based quantitative proteomics, we analyzed CSF from 73 participants included 34 PD patients, 14 PDD patients and and 25 healthy Controls (HCs). Bioinformatics analysis identified 44 differentially expressed proteins in PDD compared to PD (33 upregulated, 11 downregulated). Subsequent validation by ELISA confirmed a significant decrease in Insulin-like Growth Factor Binding Protein 3 (IGFBP3) concentration in PDD CSF compared to PD, while other candidates (NXPH1, LRRN1, HPRT1) showed no significant differences. In vitro functional studies using SH-SY5Y neuroblastoma cells demonstrated that IGFBP3 significantly attenuated cytotoxicity and apoptosis induced by the neurotoxin MPP+. IGFBP3 pretreatment improved cell viability (assessed by CCK-8 assay), reduced lactate dehydrogenase (LDH) release, and decreased apoptosis rates (measured by flow cytometry). Mechanistically, IGFBP3 counteracted MPP+-induced dysregulation of apoptosis markers (increased Bcl-2/Bax ratio; reduced cleaved caspase-3/caspase-3 ratio) and activated the PI3K/Akt/GSK3β signaling pathway by restoring phosphorylation levels of PI3K, Akt, and GSK3β.ResultsThese findings suggest that decreased CSF IGFBP3 is a potential biomarker for PDD. Furthermore, IGFBP3 exerts neuroprotective effects against MPP+ toxicity, likely mediated through the activation of PI3K/Akt/GSK3β pathway and inhibition of apoptosis.ConclusionIGFBP3 warrants further investigation as a diagnostic biomarker and therapeutic target for PDD, necessitating future validation in larger cohorts and in vivo models.